Clinical neuropsychology. - Heilman, Kenneth M., ....-; Valenstein, Edward, ....- (Oxford : University Press, 2003)
Clinical Neuropsychology comprehensively reviews the major neurobehavioral disorders associated with brain dysfunction. Since the third edition appeared in 1993 there have been many advances in the understanding and treatment of neurobehavioral disorders. This edition, like prior editions, describes the classical signs and symptoms associated with the major behavioural disorders such as aphasia, agraphia, alexia, amnesia, apraxia, neglect, executive disorders and dementia. It also discusses advances in assessing, diagnosing and treating these disorders and it addresses the brain mechanisms underlying these deficits. A multi-authored text has the advantage of having authorities write about the disorders in which they have expertise. The fourth edition adds new authors and five entirely new chapters on phonologic aspects of language disorders, syntactic aspects of language disorders, lexical-semantic aspects of language disorders, anosognosia, hallucinations and related conditions. This is the most comprehensive edition of this text to date.
Inhoudsopgave : 1. Introduction 2. Aphasic syndromes 3. Phonologic aspects of language disorders 4. Syntactic aspects of language disorders 5. Lexical-semantic aspects of language disorders 6. Acquired dyslexia 7. Agraphia 8. Disorders of visual-spatial perception and cognition 9. Acalculia and disturbances of the body schema 10. Anosognosia 11. Apraxia 12. Agnosia 13. Neglect and related disorders 14. The callosal syndromes 15. The frontal lobes 16. Emotional disorders associated with neurological diseases 17. Hallucinations and related conditions 18. Amnesic disorders19. Neuropsychology of dementia 20. Recovery of cognition 21. Pharmacotherapy of cognition
Keywords: Neuropsychologie